Electromagnetic and Mechanical Stress Analysis of a 5 MW High-Pole Non-Overlap Winding Wound-Rotor Synchronous Wind Generator - Karen S. Garner; Udochukwu B. Akuru (Energies)
Utilizing non-overlap windings has emerged as a favourable choice for minimizing electrical machine manufacturing costs, among other benefits. Nevertheless, it is widely acknowledged that these windings exhibit a notable level of harmonic contents in the resultant magnetomotive force, which can detrimentally impact machine performance, particularly in terms of torque ripple. In the context of wind energy conversion, maintaining low torque ripple is an essential and demanding prerequisite. Medium-speed wind generators present a good trade-off between high energy yield and low gearbox ratios. So far, medium-speed non-overlap winding wound-rotor synchronous generator (WRSG) technologies have been limited to 10/12 and the less common 16/18 pole/slot combinations. In this study, the analysis of a high-pole number combination (24/27 pole/slots) non-overlap WRSG is carried out to theoretically and comparatively predict the electromagnetic and radial force mechanical stress performance analysis with the 16/18 machine with a phase-shifted non-overlap winding (PSW), at 5 MW power level. The study, which is founded on the finite element analysis (FEA) technique, shows that the 24/27 machine exhibits comparable average torque and torque ripple, lower core losses and significantly reduced radial forces compared to the 16/18 PSW-WRSG. However, the 16/18 PSW-WRSG has a 50% reduction in the radial forces compared to the conventional 16/18 non-overlap winding. Experimental vibration analysis of a 3 kW 16/18 WRSG test machine confirms the radial force and vibration reduction in the phase-shifted winding.